2017
DOI: 10.1039/c7tb02364b
|View full text |Cite
|
Sign up to set email alerts
|

In vitro degradation behavior of a hydroxyapatite/poly(lactide-co-glycolide) composite reinforced by micro/nano-hybrid poly(glycolide) fibers for bone repair

Abstract: A poly(glycolide) (PGA) fiber-reinforced hydroxyapatite/poly(lactide-co-glycolide) (HA/PLGA) composite with high mechanical strength has been prepared previously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…As shown in Figure 3f, the M w of PLGA in all scaffolds decreased exponentially along with the degradation time, which was consistent with the reported results. [ 3,5,18 ] During the whole degradation process, the M w decrease of PLGA in the IO‐OA/PLGA scaffolds under AMF+ was the fastest, especially after degradation for 4 weeks. At 16th week, the M w of PLGA in PLGA, IO/PLGA, and IO‐OA/PLGA scaffolds under AMF+ (under AMF‐) decreased from about 250 KDa to 47.63 ± 0.75 (40.40 ± 1.44), 32.26 ± 6.68 (46.14 ± 4.12), and 23.52 ± 0.04 (38.92 ± 0.35) KDa, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As shown in Figure 3f, the M w of PLGA in all scaffolds decreased exponentially along with the degradation time, which was consistent with the reported results. [ 3,5,18 ] During the whole degradation process, the M w decrease of PLGA in the IO‐OA/PLGA scaffolds under AMF+ was the fastest, especially after degradation for 4 weeks. At 16th week, the M w of PLGA in PLGA, IO/PLGA, and IO‐OA/PLGA scaffolds under AMF+ (under AMF‐) decreased from about 250 KDa to 47.63 ± 0.75 (40.40 ± 1.44), 32.26 ± 6.68 (46.14 ± 4.12), and 23.52 ± 0.04 (38.92 ± 0.35) KDa, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the hydrolysis of PLGA in the degradation medium proceeds in three stages. [ 5,18 ] In the first stage, the molecular weight decreases rapidly with low mass loss. In the second stage, severe mass loss begins along with monomer formation, but the change of molecular weight decreases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The degradation products of PLGA can be absorbed and metabolized by the human body, which can minimize the potential physical interference in nerve regeneration. Those composites of effective electrical activity and biocompatibility have been widely used in tissue engineering repair research …”
Section: Introductionmentioning
confidence: 99%